2006
DOI: 10.1177/014107680609900318
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Haemophilia in Urticarial Vasculitis Revealed by Injudicious Heparin

Abstract: A swollen tender calf may be due to haematoma: be careful with anticoagulation. CASE HISTORY A 66-year-old woman had a 4½ year history of urticarial vasculitis confirmed by skin biopsy. 1 She was on long-term prednisolone 10mg/day; she had recently received a short course of colchicine. She presented to casualty with acute swelling of the left calf, which was tender, warm and firm but not, at this stage, discoloured. A deep venous thrombosis was suspected. No investigations were done at this stage (d-dimers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The cutaneous vasculitis was treated with azathioprine for 3 years. In 2006, Patel et al [ 10 ] reported on a 66-year-old patient who had been treated for 4 years for urticarial vasculitis, who was still on 10 mg prednisolone, and who developed AHA, with a favourable outcome after an increase in steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous vasculitis was treated with azathioprine for 3 years. In 2006, Patel et al [ 10 ] reported on a 66-year-old patient who had been treated for 4 years for urticarial vasculitis, who was still on 10 mg prednisolone, and who developed AHA, with a favourable outcome after an increase in steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A reported pregnant woman developed acquired reactive perforating collagenosis at the sites of resolved UV lesions 3 weeks following the onset and treatment of UV [19]. A reported UV case developed acquired hemophilia following 4.5 years of follow up [93]. Another reported NUV case first presented with acquired hemophilia and developed NUV and angioedema in the following 5 months [94].…”
Section: Course and Prognosismentioning
confidence: 99%